2004
DOI: 10.1089/107632704322791899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enhanced O2 Transport on Hepatocytes Packed within a Bioartificial Liver Device

Abstract: The functional performance of an extracorporeal bioartificial liver (BAL) device requires that suitable nutrient pathways exist to support the hepatocytes packed within it. Consequently the limited transport distance of the nutrient oxygen is a limiting factor in the scale-up of many BAL designs. In this study the porosity of a collagen extracellular matrix is increased to evaluate how enhanced O(2) transport alters the viability and functional performance of gel-entrapped hepatocytes packed within a BAL. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…The bioreactor has the additional benefit of employing a cellular space (i.e., its cartridge design) that is unique in that it offers the flexibility to easily support any anchorage-dependant cell type. It can also be modified to incorporate modifications proven to further improve functional output (e.g., O 2 transport enhancements [38][39][40] and micropatterned cocultures 27,28 ). The cartridge design also enables cells of the bioreactor to interact with the circulating medium through both of the membrane surfaces of each individual cartridge.…”
Section: Discussionmentioning
confidence: 99%
“…The bioreactor has the additional benefit of employing a cellular space (i.e., its cartridge design) that is unique in that it offers the flexibility to easily support any anchorage-dependant cell type. It can also be modified to incorporate modifications proven to further improve functional output (e.g., O 2 transport enhancements [38][39][40] and micropatterned cocultures 27,28 ). The cartridge design also enables cells of the bioreactor to interact with the circulating medium through both of the membrane surfaces of each individual cartridge.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques success in improving O 2 transport is thought to be closely related to the increased porosity of the enhanced ECM, since confocal microscopy (previously reported in McClelland and Coger, 2004) has revealed the presence of a gap thickness between the surface of each microsphere and the ECM gel that surrounds it. It is believed that the conduits for gaseous (e.g., O 2 ) transport-created by these gap thicknessesyield the improved O 2 transport distances achieved by the technique.…”
Section: Ecm Preparationmentioning
confidence: 99%
“…11 We recently developed a unique method for enhancing O 2 transport through packed-bed extracellular matrix (ECM) systems by utilizing a porous modified structure of collagen type I ECM in a concentric cylinder BAL. 12 In previous studies, [12][13][14] this ''enhanced collagen'' ECM showed superior improvement of hepatocyte viability and functions as compared with ''normal collagen'' ECM. The results also demonstrated that the enhanced collagen ECM enables a cellular space to be employed of larger dimensions than in packed-bed designs containing hepatocytes entrapped within normal collagen.…”
Section: Introductionmentioning
confidence: 87%